Perkembangan konstitusionalitas Penguasaan negara atas sumber Daya alam Dalam Putusan mahkamah konstitusi - Yance Arizona (Jurnal Konstitusi, 2016)
The economy is based on democratic economy, prosperity for everyone! Therefore, any types of production  those  are  important  for  the  state  and mastering of many people must be controlled by the state. Otherwise, the reins of production fell into the hands of powerful parties and the people become oppressed. That is the original meaning of Article 33 of Indonesia Constitution based on formal explanation of the first Indonesia Constitution. But after the formal explanation was removed, the explanation of Article 33 no longer refers to the original meaning was set up by the framer constitution. This paper discusses the development of the interpretation   of Article 33 in ‘new space’ as seen from decisions of the Constitutional Court in examining the laws over the constitution. To show how the interpretation of Article 33 by the Constitutional Court, particularly regard to the conception of state control over natural resources, this paper discuss eleven decisions of Constitutional Court dealing to review several natural resources laws.